1994
DOI: 10.1007/bf02168088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugar ingestion expectancies on mother-child interactions

Abstract: This study tested the hypothesis that commonly reported negative effects of sugar on children's behavior may be due to parental expectancies. A challenge study design was employed, in which thirty-five 5- to 7-year-old boys reported by their mothers to be behaviorally "sugar sensitive," and their mothers, were randomly assigned to experimental and control groups. In the experimental group, mothers were told their children had received a large dose of sugar, whereas in the control condition mothers were told th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…Parental expectancies have also a significant influence on both reports of child behavior and parent-child interactions. For example, manipulation information provided to the mothers who believed their sons to be behaviorally “sugar sensitive” changed mothers’ perceptions of behavior [34]. Children were given a sweet but sugar-free drink and the mothers’ perceptions of behavior, physical activity of the child (using wrist and ankle actometers) and mother-son interactions were assessed.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental expectancies have also a significant influence on both reports of child behavior and parent-child interactions. For example, manipulation information provided to the mothers who believed their sons to be behaviorally “sugar sensitive” changed mothers’ perceptions of behavior [34]. Children were given a sweet but sugar-free drink and the mothers’ perceptions of behavior, physical activity of the child (using wrist and ankle actometers) and mother-son interactions were assessed.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Children were given a sweet but sugar-free drink and the mothers’ perceptions of behavior, physical activity of the child (using wrist and ankle actometers) and mother-son interactions were assessed. Mothers who were incorrectly informed that their sons had ingested sugar rated them as more hyperactive and less compliant than those provided with accurate information [34]. Relationships between subjective and objective measures are often low, with subjective measures typically showing greater improvements in situations where parents have positive expectancies for outcomes (for a review, see ref.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…An answer was suggested by a study that concluded that the commonly reported negative effects of sucrose largely reflected parental expectations (Hoover and Milich, 1994). The parents of 5-7-year-old boys, reported to be ''sugar sensitive,'' were randomly told that their children had consumed either a high dose of sugar or a placebo.…”
Section: Challenge Studiesmentioning
confidence: 98%
“…When examining the limiting of discretionary choices, providing their child with their required nutritional intake and maintaining consistent energy levels, were the most poignant beliefs. These beliefs indicate that mothers hold the view that discretionary choice foods interrupt nutritional eating, and may give their child a sugar fix, thus making their behaviour more hyperactive (Hoover & Milich, 1994).…”
Section: Tablementioning
confidence: 99%